1998
DOI: 10.1093/ajcn/67.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in fatness in white children: no effect of childhood energy expenditure

Abstract: Reduced energy expenditure may predispose children to the development of obesity, but there are limited longitudinal studies to support this theory. We studied 75 white, preadolescent children over 4 y by taking annual measures of body composition and resting energy expenditure (by indirect calorimetry) and two annual measures of total energy expenditure and physical-activity-related energy expenditure (by doubly labeled water). Body composition of parents was assessed at the onset of the study with use of und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 33 publications
7
75
1
4
Order By: Relevance
“…Although there are good examples of an inverse relationship between obesity and physical activity in children, 81,82 and a positive relationship between obesity and physical inactivity, 83 some indices of physical activity (freeliving activity energy expenditure) are positively related to fatness and do not predict the development of body fat in children. 26 In addition, although it is generally agreed that television may be related to the onset of obesity and reduced physical activity in children, 45,59 with some prospective data suggesting that television viewing (as a marker for inactivity) in children predicts the development of obesity over time, 82 these relationships are not supported by all prior studies. 84 Laboratory studies show that ®tness and energy costs of speci®c activities are similar in lean and obese children after normalising for differences in body composition.…”
Section: Physical Activity and Obesitymentioning
confidence: 98%
See 2 more Smart Citations
“…Although there are good examples of an inverse relationship between obesity and physical activity in children, 81,82 and a positive relationship between obesity and physical inactivity, 83 some indices of physical activity (freeliving activity energy expenditure) are positively related to fatness and do not predict the development of body fat in children. 26 In addition, although it is generally agreed that television may be related to the onset of obesity and reduced physical activity in children, 45,59 with some prospective data suggesting that television viewing (as a marker for inactivity) in children predicts the development of obesity over time, 82 these relationships are not supported by all prior studies. 84 Laboratory studies show that ®tness and energy costs of speci®c activities are similar in lean and obese children after normalising for differences in body composition.…”
Section: Physical Activity and Obesitymentioning
confidence: 98%
“…Although recent metabolic and genetic research has deepened our understanding of the physiological aspects of body weight regulation, there is very little evidence to support the concept that the development of obesity in children is determined by acute metabolic andaor genetic defects. 25,26 It is extremely unlikely that acute changes in the gene pool or alterations in metabolic rate have arisen and are responsible for the recent increase in obesity prevalence in the population. A more plausible explanation for the increasing prevalence of obesity relates to cultural changes accompanying societal development, such as a decreased requirement for physical activity and greater abundance and availability of food.…”
Section: Epidemiology and Health Consequences Of Pediatric Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] However, reduced energy expenditure alone cannot explain the gain of fat mass during growth. 19,20 On the other hand, increased levels of physical activity are associated with a lower BMI in youths. [21][22][23] Exercise interventions in prepubertal obese children have already demonstrated that physical training during a short period of time (few months) has a favourable impact on body composition and some obesity-associated health factors.…”
Section: Introductionmentioning
confidence: 99%
“…Existing cross-sectional and longitudinal studies report inconsistent findings, both in children and adults; some report a protective effect of physical activity against obesity, others find no association and a few have suggested that higher activity is related to increased fatness. [1][2][3][4] This lack of consistency is likely to be partly due to the variety of methods used to measure body fat and energy expenditure or physical activity, but may also be due to gender, age and sociocultural differences in type or range of physical activity. In the UK, girls are only slightly less active than boys up to the age of about 7 y, but from then on through into adulthood, female subjects are noticeably less active than males, 5 a gender difference that is common across the Western world.…”
Section: Introductionmentioning
confidence: 99%